Construção de uma ferramenta gerencial de autodiagnostico: o engaged scholarship e a aprendizagem por meio do uso - Portes, Marcus Vinicius Massignan (2019)
Objective of the work: Due to the existence of a gap between researchers and practitioners in management areas and the fact that this gap is more evident in small and medium-sized companies, the objective of this study was to construct a self-diagnostic tool based on the approach of the engaged scholarship, with its main focus on the use of business management tools by small and medium-sized companies. Design / Methodology / Approach: This work is classified as an applied research that contribute to reduce the gap between academic research and professional practices using the engaged research approach. Results: The result was to make this self-diagnostic tool available to the public on the link http: //201.6.243.44:2875/controladoria. This tool provides a diagnostic to the managers of micro and small business, situating their exposure to operational risks by providing diagnostics relation to the safety margin used by the Company and the low diversification in clients. The interactive tool also provides recommendations for the managers regarding the importance of managerial control techniques. Practical Implications: The results should be analyzed considering the limitations of this work, which developed an interactive self-diagnosis tool that sought to analyze the safety margin used and the degree of customer diversification used by small companies. The main gain was the dissemination of knowledge and the reduction of the gap between researchers and practitioners.